Center‐Periphery Bargaining in the Age of Democracy. Issue 4 (25th November 2016) - Siroky, David S.; Mueller, Sean; Hechter, Michael
Abstract: This paper introduces the key concepts used in this special issue – center, periphery, and vertical bargaining – and inquires why some national groups within democratic states demand outright independence, while others mobilize for regional autonomy and still others settle for even less. It then specifies a theoretical framework that tries to explain cross‐sectional differences and temporal changes in both peripheral demands and central responses. The building blocks of that framework include cultural distinctiveness, credibility of the exit threat and central dependence on the periphery. As an empirical illustration, the paper discusses the case of the Bernese Jura in Switzerland, and then briefly introduces the contributions to this special issue.